Short-term associations between fine and coarse particles and hospital admissions for cardiorespiratory diseases in six French cities. Issue 8 (4th December 2007) - Host, S; Larrieu, S; Pascal, L; Blanchard, M; Declercq, C; Fabre, P; Jusot, J-F; Chardon, B; Le Tertre, A; Wagner, V; Prouvost, H; Lefranc, A
Abstract : Objectives: Little is known about the potential health effects of the coarse fraction of ambient particles. The aim of this study is to estimate the links between fine (PM2.5 ) and coarse particle (PM2.5−10 ) levels and cardiorespiratory hospitalisations in six French cities during 2000–2003. Methods: Data on the daily numbers of hospitalisations for respiratory, cardiovascular, cardiac and ischaemic heart diseases were collected. Associations between exposure indicators and hospitalisations were estimated in each city using a Poisson regression model, controlling for confounding factors (seasons, days of the week, holidays, influenza epidemics, pollen counts, temperature) and temporal trends. City-specific findings were combined to obtain excess relative risks (ERRs) associated with a 10 μg/m 3 increase in PM2.5 and PM2.5−10 levels. Results: We found positive associations between indicators of particulate pollution and hospitalisations for respiratory infection, with an ERR of 4.4% (95% CI 0.9 to 8.0) for PM2.5−10 and 2.5% (95% CI 0.1 to 4.8) for PM2.5 . Concerning respiratory diseases, no association was observed with PM2.5, whereas positive trends were found with PM2.5−10, with a significant association for the 0–14-year-old age group (ERR 6.2%, 95% CI 0.4 to 12.3). Concerning cardiovascular diseases, positive associations were observed between PM2.5 levels and each indicator, although some did not reach significance; trends with PM2.5−10 were weaker and non-significant except for ischaemic heart disease in the elderly (ERR 6.4%, 95% CI 1.6 to 11.4). Conclusions: In accordance with other studies, our results indicate that the coarse fraction may have a stronger effect than the fine fraction on some morbidity endpoints, especially respiratory diseases.